Fundamentals of Entrepreneurship ETR300 Pineapple Farm / Najid Najmudin Abdul Rahim… [et al.] - Abdul Rahim, Najid Najmudin; Mhd Taha, Muhammad Ariff; Mohd Salim, Mohd Farhan; Ahmad, Abdul Qudus (2019)
Our company name is Pineapple Farm. We use partnership form for our business where there is consisting of four partners. Each partner share and contributes same amount of capital as agreed in our agreement. The business will be place at Samarahan and it will commence beginning 2nd May 2009. All partners are participate in the business management. We all agreed that our company is lead by Najid Naimudin Bin Abdul Rahim as a General Manager and also Administration Manager, while Muhammad Ariff Bin Mhd Taha as Marketing Manager, Mohd Farhan Bin Mohd Salim as Operation Manager and Abdul Qudus Bin Ahmad as Financial Manager.